1999
DOI: 10.1021/ma981533j
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Substituted Acetylenes and Diacetylenes:  Convenient Polymerization As Studied by Differential Scanning Calorimetry, FT-IR, and UV−vis Spectroscopy

Abstract: A series of phthalimide-and 1,12-benzoperylene-1′,2′-dicarboxylic imido-linked alkynes were prepared and analyzed by UV, FT-IR, optical microscopy, and differential scanning calorimetry. The possibility to convert ω-alkynes (R-(CH 2)n-CtCH) to diacetylenic compounds (R-(CH2)nCtC-CtC-(CH2)n-R) was investigated for R ) phthalimide and 1,12-benzoperylene-1′,2′-dicarboxylic imide with n ) 1, 3, and 9. Formation of the diacetylenic compound is usually straightforward (as checked by comparison with independently syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…Previous studied showed that 1,2-polymerisation led to a polydiacetylene structure with an IR-active (asymmetric) alkyne bond, which in turn resulted in the presence of a single stretching band at a high wavenumber in the FTIR spectrum. [41,42] The large decrease in intensity of two stretching bands by the same proportion indicates that 1,4-polymerisation proceeded to a large extent along the column axis by UV irradiation.…”
Section: Photopolymerisation and Core Extraction Of Star-shaped Supramentioning
confidence: 96%
“…Previous studied showed that 1,2-polymerisation led to a polydiacetylene structure with an IR-active (asymmetric) alkyne bond, which in turn resulted in the presence of a single stretching band at a high wavenumber in the FTIR spectrum. [41,42] The large decrease in intensity of two stretching bands by the same proportion indicates that 1,4-polymerisation proceeded to a large extent along the column axis by UV irradiation.…”
Section: Photopolymerisation and Core Extraction Of Star-shaped Supramentioning
confidence: 96%
“…Dioxygen (99.994%, BOC gases) was dried by passing the gas stream through a column of Drierite. The compounds 1-amino-5-pentyne (NH 2 (CH 2 ) 3 CCH) [22,23], Fe(OTf) 2 AE 2MeCN [24], and [Fe 2 (l-O 2 CAr Tol ) 2 (O 2 CAr Tol ) 2 (THF) 2 ] (THF = tetrahydrofuran) [25], were prepared as described in the literature. 2,6-Di(3,5-dimethylphenyl)benzoic acid (Ar Xyl CO 2 H) was synthesized by a procedure analogous to that used to make 2,6-di(p-tolyl)benzoic acid [26][27][28], and the purity was checked by 1 H NMR spectroscopy.…”
Section: General Considerationsmentioning
confidence: 99%
“…One of the most attractive materials for the fabrication of novel colourchanging based sensing devices is constituted by polydiacetylenes (PDAs), a class of π-conjugated polymers particularly promising for its unique optical and rapid stimuli-response properties [2]. The practical use of PDAs in sensoristics arises from their aptitude to undergo a blue-to-red visible color change in response to environmental perturbations [3], mechanical stress [4], and presence of specifically-targeted chemical [5] and biological [6] species. Under proper conditions, PDAs form vesicles or molecular films and can also behave as "synthetic membranes" [7], but their highest sensing potential is reached when they are self-assembled onto solid supports.…”
Section: Introductionmentioning
confidence: 99%